Association between serum vitamin D and the risk of diabetic kidney disease in patients with type 2 diabetes - Wang, Yujie; Hu, Chenggang; Li, Ying; Liu, Qi; Gao, Lichao; Zhang, Dongmei; Cao, Ling (Frontiers in Medicine, 2024)
Aims: This investigation explored the potential correlation between serum vitamin D concentration and diabetic kidney disease (DKD) among patients with type 2 diabetes mellitus (T2DM).Methods: This cross-sectional study assessed 4,570 patients with T2DM drawn from the National Health and Nutrition Examination Survey (NHANES) dataset. Restricted cubic splines were utilized to examine the dose-response relationship between serum vitamin D levels and the risk of DKD in patients with T2DM. Serum vitamin D concentrations were divided into quartiles for multivariable logistic regression analysis to evaluate the association between varying serum vitamin D levels and DKD risk in patients with T2DM. Additionally, sex-stratified analyses were conducted to determine consistency of the results. The influence of vitamin D concentrations on mortality risk was assessed using a Cox regression model.Results: Of the patients with T2DM, 33% were diagnosed with DKD. Restricted cubic spline plots revealed a U-shaped relationship between vitamin D levels and DKD risk, with a protective effect noted in the mid-range, indicating optimal serum vitamin D concentrations between 59.6 nmol/L and 84.3 nmol/L. The multivariate Cox regression analysis suggested that higher VID levels were associated with a reduced mortality risk, particularly in male patients.The regulation and monitoring of serum vitamin D levels within an optimal range may play a pivotal role in the prevention of DKD in patients with T2DM. Public health strategies should emphasize the regular monitoring of vitamin D levels, especially among populations at elevated risk, to mitigate the progression of DKD and decrease the associated mortality rates.